Peran Conflict of Interest: Analisis Korupsi 271T oleh Harvey Moeis - Natatsa Salsabila; Khalisya Putri Koeswanti; Rafsya Aulia Putri; Yoana Khairunissa Santi; Ida Farida Adi Prawira (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Conflicts of interest in corruption cases often involve abuse of power for personal gain. This article discusses the corruption case committed by Harvey Moeis with an emphasis on how conflicts of interest play a role in the occurrence of corruption. The purpose of this study is to analyze the link between conflicts of interest and corruption cases involving Harvey Moeis, its impact on law, ethics, and reputation, as well as find solutions to prevent similar cases. The methods used were purposive sampling in the selection of data sources as well as literature study to analyze related perspectives. The results of the analysis reveal that the corruption case involving Harvey Moeis demonstrates how financial conflicts of interest can culminate in abuses of power that harm the state and tarnish the law, ethics, and reputation. Strengthening regulation, transparency, law enforcement, and public participation as well as strengthening anticorruption institutions is therefore needed to prevent corrupt practices.